Influence of enzyme location and culture rheology on glucose oxidase production and recovery by Aspergillus niger NRRL-3 and Penicillium sp. CBS120262 Madelyn Johnstone-Robertson. - Johnstone-Robertson, Madelyn (Centre for Bioprocess Engineering Research, 2015)
Includes synopsis.